Horrid Henry and the demon dinner lady - Simon; Francesca (London Orion Children's, 2013)
Horrid Henry is furious! No way will Greasy Greta, the dinner lady, snatch his delicious sweets and crisps again. He tries hiding his food. He tries eating his desserts secretly. But it is no use. So Horrid Henry starts to plan his revenge